2009
DOI: 10.1007/s11276-009-0223-9
|View full text |Cite
|
Sign up to set email alerts
|

A wireless access network based on WDM-PON for HMIPv6 mobility support

Abstract: In this paper, an IP-based wireless access network is proposed, which is designed to support the hierarchical MIPv6 standard on the wavelength division multiplexed passive optical network access network in order to provide a fast and seamless handoff support. Two schemes for enhancing the mobility management are included in the proposed network's infrastructure support. Firstly, the local-link channels between sub-networks are provided to improve the mobility management efficiency for the mobile nodes roaming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, it is found that traditional networks do not meet the foremost carrier requirements for future worldwide fiber access. This includes management, flexibility and upgradability of bandwidth, higher capacity, maximum reuse of existing optical distribution network (ODN), higher split ratio and capacity than existing deployed standards (Lee et al 2010). Hence, in 2012, the next-generation PON (NG-PON) based 40 Gbps time and wavelength division multiplexed PON (TWDM-PON) network has been proposed and demonstrated (Kaur et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is found that traditional networks do not meet the foremost carrier requirements for future worldwide fiber access. This includes management, flexibility and upgradability of bandwidth, higher capacity, maximum reuse of existing optical distribution network (ODN), higher split ratio and capacity than existing deployed standards (Lee et al 2010). Hence, in 2012, the next-generation PON (NG-PON) based 40 Gbps time and wavelength division multiplexed PON (TWDM-PON) network has been proposed and demonstrated (Kaur et al 2017b).…”
Section: Introductionmentioning
confidence: 99%